2021
DOI: 10.1186/s12876-021-01884-5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of non-HBV- and non-HCV-related hepatocellular carcinoma: single-institution 20-year study

Abstract: Background We previously reported on the trends in the etiologies of hepatocellular carcinoma (HCC) diagnosed in patients between 1995 and 2009. The aims of our updated study were to evaluate the incidence, nonhepatitis B and nonhepatitis C viral (NBNC) etiologies, and clinical characteristics of HCCs occurring in patients between 1992 and 2018. Methods The study enrolled 2171 consecutive patients with HCC between 1992 and 2018. Their medical reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…Moreover, when we further investigated the assessment criteria for MAFLD, the patients with NBNC-HCC in the second five-year period were significantly older, and had a higher frequency of T2DM, hypertension, and higher BMI compared to the patients with HBV-HCC. This result is similar, but not exactly the same, as recently published Japanese study ( 41 ). Nagaoki et al.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, when we further investigated the assessment criteria for MAFLD, the patients with NBNC-HCC in the second five-year period were significantly older, and had a higher frequency of T2DM, hypertension, and higher BMI compared to the patients with HBV-HCC. This result is similar, but not exactly the same, as recently published Japanese study ( 41 ). Nagaoki et al.…”
Section: Discussionsupporting
confidence: 91%
“…Non-B non-C HCC is now becoming the leading cause of HCC in many countries of the Asia-Pacific region following the control and treatment of viral hepatitis [ 30 , 53 , 93 - 96 ]. Eighty-five percent of patients with non-B non-C HCC have at least one risk factor for MAFLD, suggesting that it is the dominant etiology for non-B non-C HCC [ 97 ].…”
Section: Mafld-related Hcc: a Proposed New Classification For The Eti...mentioning
confidence: 99%
“…However, the incidence of HCC in patients who are negative for HCVAb and HBsAg (NBNC-HCC) has gradually increased from 19% in 2009 to 35% in 2018. 3 Tateishi et al reported that the incidence of NBNC-HCC has increased from 10% in 1991 to 32.5% in 2015. 4,5 Therefore, increasing numbers of patients with NBNC-HCC related to NAFLD have recently become a serious problem in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HCV‐related HCC has gradually decreased. However, the incidence of HCC in patients who are negative for HCVAb and HBsAg (NBNC‐HCC) has gradually increased from 19% in 2009 to 35% in 2018 3 . Tateishi et al.…”
Section: Introductionmentioning
confidence: 99%